Respuesta :
−5p+20
= −5p+4(5)
= -(5p-4(5))
= -5(p-4)
To check if you did it right, use expansions
-5(p-4)
= -5(p) -5(-4)
= -5p +20
= −5p+4(5)
= -(5p-4(5))
= -5(p-4)
To check if you did it right, use expansions
-5(p-4)
= -5(p) -5(-4)
= -5p +20
Answer:
-5(p-4)
Step-by-step explanation:
You just need to found a common factor between the two terms, and you divide the function by the common factor:
-5p+20, so the maximum common factor would be -5 in order to leave the P alone:
[tex]-5\sqrt{(-5p+20} \\\frac{-5p+20}{-5}=p-4[/tex]
So both factors would be -5(p-4)